Functional-Environmental Evaluation of Pocket Parks in Urbanized Areas - The Case Study of Gliwice - Bradecki, Tomasz; Opania, Szymon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the role and importance of creating new green areas in the areas of urban agglomerations. Particular attention was paid to the processes of creating new green areas in post-industrial areas and urban wastelands and their restoration for cities. The issue of the formation of pocket parks is raised and the results of the detailed research carried out by the authors in 2020 are briefly discussed.
Keywords: pocket park; landscape architecture; revitalisation of urban spaces; green spaces in cities; park kieszonkowy; architektura krajobrazu; rewitalizacja przestrzeni miejskiej; tereny zieleni miejskiej